2020
DOI: 10.1177/0033354920953209
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous Reporting of Deaths Attributed to Pneumonia and Influenza at 2 New York City Teaching Hospitals, 2013-2014

Abstract: Objectives Cause-of-death information, reported by frontline clinicians after a patient’s death, is an irreplaceable source of public health data. However, systematic bias in cause-of-death reporting can lead to over- or underestimation of deaths attributable to different causes. New York City consistently reports higher rates of deaths attributable to pneumonia and influenza than many other US cities and the country. We investigated systematic erroneous reporting as a possible explanation for this phenomenon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Future work examines full combinations of conditions which allow for mutually exclusive category reporting. The usual caveats concerning the potential incompleteness of death certificate data also apply 39–44. Common mistakes may include improbable sequencing, and the listing of non-specific conditions or processes as underlying cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work examines full combinations of conditions which allow for mutually exclusive category reporting. The usual caveats concerning the potential incompleteness of death certificate data also apply 39–44. Common mistakes may include improbable sequencing, and the listing of non-specific conditions or processes as underlying cause.…”
Section: Discussionmentioning
confidence: 99%
“…The usual caveats concerning the potential incompleteness of death certificate data also apply. [39][40][41][42][43][44] Common mistakes may include improbable sequencing, and the listing of non-specific conditions or processes as underlying cause. Quality control efforts have allowed us to use the most complete and accurate data available for this analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Conversely, a small study conducted in two teaching hospitals in New York City, USA, retrospectively reviewed all deaths with pneumonia or influenza as the cause of death and found that more than one-third were, in fact, due to heart disease or dementia/Alzheimer’s disease. 66 …”
Section: Discussionmentioning
confidence: 99%
“…Which health-related disciplines were not represented? The Task Force included no experts in behavioral sciences or education, despite the effects of its decisions on mental health service delivery, substance use disorder treatment, and schools and universities [35] , [36] , [37] ; none in decision analytic modeling, despite the influence of nonpeer-reviewed models using controversial methods on governmental decisions [38] , [39] , [40] ; none in risk communication, despite a recognized need to explain public health risks and risk-mitigation policies effectively, using known best practices derived from psychological science [41] ; and none in health informatics, despite known inaccuracies and coding biases in the cause-of-death data on which the Task Force relied [42] , [43] , [44] .…”
Section: Introductionmentioning
confidence: 99%